KETERAMPILAN MENULIS TEKS EKSPOSISI MENURUT PERSPEKTIF KELAS PARALEL - Lina Siti Nurwahidah; Deasy Aditya Damayanti; Agus Hamdani; Abdul Hasim; Abdul Razak (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article describes students’ writing skills in expository text based on the parallel class perspective for first-grade high school students. The research took place at the beginning of the even semester 2021/2022. The research used a descriptive-quantitative method. The population of the research were all students of class X SMA Negeri 6 Karawang who submitted answers to the writing skills test via a google form, which consisted of 137 students. There were 102 students who were selected through a simple random technique. Data were analyzed by using parametric inferential statistics with one sample t-test and a one-way Anova test via SPSS. The requirements for the homogeneity of variance and the normality of the curves of the Lilifors testing method were fulfilled through SPSS completely. It was found that the t-test of one sample was 0.411 at sig. 0.682 so that sig. 0.682 > 0.05, which means that the mean observation was 6.05 similar to the estimated mean of 6.00. The observed mean of 6.05 was equivalent to a relative value of 41.21%. This percentage included the low category. F value = 0.134 in sig. 0.970, so that sig. 0.970 > 0.05, which means that there is no difference in the mean of writing skill in writing exposition texts between class X-1, class X-2, class X-3, class X-4, and class X-5. The results contributed to related institutions regarding learning to write expository texts in a context of a gender perspective and parallel classes.